Uncovering Olive Biodiversity through Analysis of Floral and Fruiting Biology and Assessment of Genetic Diversity of 120 Italian Cultivars with Minor or Marginal Diffusion - Luca Lombardo; Gianni Fila; Nicola Lombardo; Chiara Epifani; Donald H. Duffy; Gianluca Godino; Amelia Salimonti; Samanta Zelasco (Biology, 2019)
The primary impetus behind this research was to provide a boost to the characterization of the Italian olive biodiversity by acquiring reliable and homogeneous data over the course of an eight-year trial on the floral and fruiting biology of 120 molecularly analyzed cultivars, most of which have either low or very low diffusion. The obtained data highlighted a considerable variability to almost all of the analyzed parameters, which given the uniformity of environment and crop management was indicative of a large genetic variability in the accessions under observation, as confirmed through the molecular analysis. Several cases of synonymy were reported for the first time, even among plants cultivated in different regions, whilst all of the varieties examined, with only one exception, showed very low percentages of self-fruit-set, indicating a need for the employment of suitable pollinator plants. Eventually, a fitted model allowed us to evaluate the clear effects of the thermal values on blossoming, particularly in the months of March and April, whereas the climatic conditions during the flowering time had only a modest effect on its duration.